HUBUNGAN PERCAYA DIRI DENGAN KREATIVITAS GURU DI TK SE-KELURAHAN TANGKERANG KECAMATAN MARPOYAN DAMAI PEKANBARU RIAU - Rahmah Rahmah; Dona Novianti (Jurnal Ilmiah Visi, 2017)
This study aims to find out correlation between self-confidence and teachers’ creativity at kindergarten schools in Kelurahan Tangerang, Kecamatan Marpoyan Damai, Pekanbaru. This study uses quantitative method. This study was taken place at kindergarten schools in Kelurahan Tangkerang in Pekanbaru. Populations were all kindergarten teachers in that region which consisted of 122 kindergarten teachers from 17 kindergarten schools. Samples taken in this study were 55 kindergarten teachers in Tangkerang sub-district Marpoyan Damai sub-district Pekanbaru from April to June 2016. Based on data analysis obtained, it can be inferred that correlation coefficient (R) equal to 761, thus the value of R Square = 579 which means self-confidence variable gives 76.1% influence on teachers’ creativity, meanwhile the rest equal to (100% - 76.1) = 23.9% influenced by other factors out of variables examined. Due to t hitung > t table (8.546>2.007) then Ho is rejected which means there is significant correlation between self-confidence and teachers’ creativity.